Pineapple Grenade : Serge A. Storms #15 - Dorsey, Tim (New York : William Morrow, 2012)
After a gutless corpse called "Hollow Man" is found on the beach and giant shark carcasses stuffed with human limbs clog up busy intersections, one-man vigilante Serge Storms, determined to be a spy, decides to investigate.
Keywords: Storms, Serge (Fictitious character) -- Fiction; Storms, Serge (Fictional character); Florida -- Fiction; Florida -- Fiction; Spy fiction; Humorous fiction